Length- weight relationship, condition factor and sex ratio of Oreochromis niloticus and Chrysichthys nigrodigitatus in the lower section of Osun River, Nigeria - Iyiola, Adams Ovie; Kolawole, Ayotunde Samuel; Umma, Samuel Bem; Iriobe, Tosin (Aceh Journal of Animal Science, 2024)
Osun River is a major river in the Ogun-Osun River Basin and contributes significantly to fish production and quality source of protein. It is therefore essential to investigate the condition and characteristics of the most abundant fish species in the river. This aim was achieved by investigating the Morphometric parameters, sex ratio, and condition factor of Oreochromis niloticus and Chrysichthys nigrodigitatus in the lower section of the river; because these fish species were the most abundant and economically important. Monofilament gillnets were used for fish sampling for twelve months to cover both wet and dry seasons (November 2017 to October 2018). A total of 1597 individuals of both species were collected comprising 40.13% O. niloticus samples and 59.87% samples of C. nigrodigitatus. The correlation coefficient (r) for O. niloticus and C. nigrodigitatus were 0.78 and 0.89 which indicated a high and very high relationship respectively. O. niloticus showed a significant negative allometric growth pattern (b = 2.315) while C. nigrodigitatus showed a growth pattern that was significant and positively allometric (b = 3.102). The mean condition factor (K) was 2.8 for O. niloticus and 1.9 for C. nigrodigitatus. The sex ratio of male to female was 1.5:1 for O. niloticus and 1.2:1 for C. nigrodigitatus. It can be said that both fish species responded well in the river and it is therefore essential to maintain optimal environmental factors for the sustainability of these fish species in the river.